The thousandth man : a biography of James McGregor Stewart - Cahill, Barry (Osgoode Society., 2000)
"James McGregor Stewart (1889-1955) was perhaps the foremost Canadian corporate lawyer of his day. He was also an appellate counsel, venture capitalist, Conservative Party fundraiser, bibliographer of Rudyard Kipling, and sometime university teacher of classics. A leader of the bar in the inter-war period, he was the first Maritimer to serve as president of the Canadian Bar Association. He distinguished himself mainly in constitutional cases before the Judicial Committee of the Privy Council. During his career, Stewart was also head of the leading law firm in eastern Canada (now Stewart McKelvey Stirling Scales), director and vice-president of the Royal Bank of Canada, and senior counsel to the Royal Commission on Dominion-Provincial Relations." "This biography provides both a history of a uniquely Canadian career and an interpretation of its significance for Stewart's time and ours."--Jacket.